Genesis of Hurricane Sandy (2012) simulated with a global mesoscale model. Issue 18 (19th September 2013) - Shen, B.‐W.; DeMaria, M.; Li, J.‐L. F.; Cheung, S.
<x xml:space="preserve">Abstract</x> [1] In this study, we investigate the formation predictability of Hurricane Sandy (2012) with a global mesoscale model. We first present five track and intensity forecasts of Sandy initialized at 00Z 22–26 October 2012, realistically producing its movement with a northwestward turn prior to its landfall. We then show that three experiments initialized at 00Z 16–18 October captured the genesis of Sandy with a lead time of up to 6 days and simulated reasonable evolution of Sandy's track and intensity in the next 2 day period of 18Z 21–23 October. Results suggest that the extended lead time of formation prediction is achieved by realistic simulations of multiscale processes, including (1) the interaction between an easterly wave and a low‐level westerly wind belt (WWB) and (2) the appearance of the upper‐level trough at 200 hPa to Sandy's northwest. The low‐level WWB and upper‐level trough are likely associated with a Madden‐Julian Oscillation.